The Organoleptic Acceptance Test Of Flawless Bread With Sorghum Flour Substitution - Nafies, Dian; Fauziah, Lilia Faridatul; Royyifi, Ahmad David; Sukmawati, Kartika Dewi (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Introduction. Iron-deficiency anemia is a hematological disease that is often found in pregnant women. This situation can certainly hinder the growth and development of the fetus in pregnant women. It can be said to be anemia if the number of red blood cells or hemoglobin is below the normal limit if the hemoglobin level is <14 g/dL in men and <12 g/dL in women. Therefore, food that contains iron is needed to meet daily iron needs. Sorghum planting is often found in East Java and surrounding areas. This plant contains high levels of iron compared to other cereals, such as rice. This research aims to determine the effect of sorghum flour substitution on the organoleptic acceptability of sorghum white bread. Metode. The analysis used in this research consists of static analysis and organoleptic analysis. Result&Analysis.The results of this study showed that there was a significant effect on the color, smell, flavor, and texture of white bread substituted for sorghum kurskal wallis flour (p > 0.005).Discussion. This research concludes that white bread substituted for sorghum flour influences organoleptic quality.